Eurípedes Barsanulpho e o Collégio Allan Kardec capítulos de história da educação e a gênese do espiritismo nas terras do Alto Paranaíba e Triângulo Mineiro (1907/1918) - Brettas, Anderson Claytom Ferreira (2006)
In the beginning of the XX century it emerged in the city of Sacramento, a little city of Alto Paranaíba mineiro a singular and pioneer school, baseded int the French spiritualism principles, Collégio Allan Kardec, which was founded and directed by a teacher that became a symbol of this philosophical and religious doctrine very disseminated in the Brazilian culture and identity, Eurípedes Barsanulfo. This dissertation has as principle objective the ransom of the memory of this school during the period thas was lived by Barsanulfo, since the creation in 1.907 until Barsanulfo`s death, in 1.918, analysing in what dimension the imaginary and the collective representations of the doctrine that was professed and written in the institution`s nomenclature were effectivetly implanted and lived in its quotidian. Our theoritical base is the reference in the line of search history of the scholastic institutions, wich methodology was originated in the important rupture which was realizeted in the theoretical`s reflections by studious French of New History with the traditional manner of aproach of this sciense, this studious amplified the notability of their objects and sources of investigation. History isn`t broken, but it is integral; it unites the society, the economy, the culture, the policy, the education, at last, all the sphires of the human existence correlated. In this perspective, we investigate in this research the inquiry of the historical, philosophical and conceptual origens of the spiritualistic doctrine, as well as the trajectory of Allan Kardec, which is a pseudonym that was adopted at the period of the conversion to the doctrine of the study of the dead`s world by Hippolyte Léon-Denizard Rivail, who was as important educator with a curriculum of services engaged in the improvement of the teaching and of education of his country. This is the first chapter that focuses on pointing the base found of the masters that preced Kardec in the spiritualistic pedagogy, Comenius, Rousseau and Pestalozzi. In the second chapter, we delineate in a historical and sociological perspective arrival of the spiritist in Brazil and its notable dissemination that itself united to national identity and a popular representations. In the third chapter, we will stdy the history of the country`s education and focalize on the economical and social transformations in Brazil during the transition of the Monarchy to the Republic, wich was amoment in which occured a gradual change from as agrarian and exporting society to an urban and industrial one. This was a phenomenon that was represented by na enthusiasm for the expansion of the instruction and the education, which was a tendency by the discourse and action of the various social actors, as the intellectual involved in the formatiton of a determined national spirit. Finally, in the fourth and fifth chapters we walk for the investigation of important aspects of the regional history and education`s history in Triângulo Mineiro, boarding the origens of Sacramento and central region of Brazil, its social and economical developments, the carious faces of the actuation of the citizen and religious militant Eurípedes Barsanulfo; the stages of the implantation of schools at the city; and the construction, development, schoolar quotidian and pedagogical practices of Collégio Allan Kardec, thas was the pioneer of the denominated spiritualistic pedagogy.